2017
DOI: 10.1002/jcb.26356
|View full text |Cite
|
Sign up to set email alerts
|

Genistein represses PEPCK‐C expression in an insulin‐independent manner in HepG2 cells and in alloxan‐induced diabetic mice

Abstract: Genistein has been reported to exert beneficial effects on type 2 diabetes mellitus (T2DM); however, the underlying molecular mechanisms involved therein have not been clearly elucidated. To address this question, the effect of genistein on the expression of phosphoenolpyruvate carboxykinase (PEPCK), and glucose production in HepG2 cells and in alloxan-induced diabetic mice was investigated. HepG2 cells were exposed to different concentration of genistein in presence or absence of modulators, and the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Our LC-MS analysis shows that in addition to DNJ, MLE contains genistein glycoside, kaempferol glycosides, and caffeoylquinic acid derivatives. Previous studies have shown that genistein is responsible for suppressed hepatic gluconeogenesis and increased insulin secretion ( 16 , 17 ), kaempferol stimulates insulin secretion and exerts insulinotropic effects ( 18 , 19 ), and caffeoylquinic acid is effective in stimulating glucose transport in muscle cells by activating AMPK and Akt ( 20 ). These results suggest that the antidiabetic effects of MLE in db/db mice may be mediated by not only DNJ but also a combination of several constituents of MLE.…”
Section: Discussionmentioning
confidence: 99%
“…Our LC-MS analysis shows that in addition to DNJ, MLE contains genistein glycoside, kaempferol glycosides, and caffeoylquinic acid derivatives. Previous studies have shown that genistein is responsible for suppressed hepatic gluconeogenesis and increased insulin secretion ( 16 , 17 ), kaempferol stimulates insulin secretion and exerts insulinotropic effects ( 18 , 19 ), and caffeoylquinic acid is effective in stimulating glucose transport in muscle cells by activating AMPK and Akt ( 20 ). These results suggest that the antidiabetic effects of MLE in db/db mice may be mediated by not only DNJ but also a combination of several constituents of MLE.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoenolpyruvate carboxykinase (PEPCK) activity regulate normal blood glucose levels and has been shown to be increased in diabetic animal models. Dkhar et al [284] investigated the effect of genistein on the expression of PEPCK and glucose production in alloxan-induced diabetic mice. Genistein (50 mg/kg body weight) reduced fasting glucose levels, PEPCK-C expression and increased AMPK and ERK 1/2 phosphorylation states in the liver of the genistein-treated alloxan-induced diabetic mice [284].…”
Section: Potential Health Benefitsmentioning
confidence: 99%
“…Dkhar et al [284] investigated the effect of genistein on the expression of PEPCK and glucose production in alloxan-induced diabetic mice. Genistein (50 mg/kg body weight) reduced fasting glucose levels, PEPCK-C expression and increased AMPK and ERK 1/2 phosphorylation states in the liver of the genistein-treated alloxan-induced diabetic mice [284]. The same study also showed that glucose production in HepG2 cells was reduced by about 50% in cells treated with genistein (30 µM).…”
Section: Potential Health Benefitsmentioning
confidence: 99%
“…Therefore, genistein may exert an antidiabetic role in T2DM by improving the lipid and glucose metabolism. Furthermore, Dkhar et al [77] reported that genistein reduced fasting glucose, inhibited cytosolic phosphoenolpyruvate carboxykinase (PEPCK), and activated AMPK and ERK1/2 pathway in alloxan-induced diabetic mice, which may in turn improve dysfunction in hepatic gluconeogenesis in T2DM. Furthermore, recent studies have shown that genistein might also be a prospective therapeutic approach for the management of T2DM complications [78, 79].…”
Section: Effects Of Bioactive Compounds On T2dm and Ad And Their Mmentioning
confidence: 99%
“…(8) Some bioactive compounds reduce NFT levels by inhibiting tau hyperphosphorylation. References: [46, 47, 50, 54, 55, 59, 61, 62, 64, 72, 75, 77, 81, 89, 93, 98, 101, 103, 108, 110, 116, 117, 121, 123, 126, 132, 133, 139, 140, 147, 149, 151, 152, 159, 162, 169, 175, 180, 183, 186, 189, 194196, 200, 204, 215, 217, 227, 231, 234].…”
Section: Figurementioning
confidence: 99%